PEMBINAAN KARAKTER MELALUI KAJIAN KEAGAMAAN DI PERUMAHAN MUTIARA MAS BENTENG KECAMATAN CAMPAKA - Nurarita Nurarita; Dyah Wulandari (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service article aims to improve friendship and change the character of the poor community into good ones at the Majelis Taklim Darussalam Mutiara Mas Housing Village Benteng Village, Campaka District, Purwakarta Regency. This is based on the fact that local people have poor behavior and lack of communication, differences in character and the economy make small problems complicated. The service method uses the Participatory Action Research (PAR) method, firstly conducting observations and interviews to fill out questions related to the character of the community, secondly analyzing the problems that occur then continuing with taking actions in the form of recitations at the Taklim Majelis every Saturday afternoon and every activity carried out by researchers observe every character of society.